Combinations of Peptide-Protein Extracts from Native Probiotics Suppress the Growth of Multidrug-Resistant Staphylococcus aureus and Citrobacter freundii via Membrane Perturbation and Ultrastructural Changes - Gabriela N. Tenea; Evelyn Angamarca; Daniela Olmedo (MDPI AG, 2022)
The occurrence of multidrug-resistant pathogens in the food chain causes health problems in humans, thus, research for novel antimicrobials to combat their growth is of interest. This study evaluates the antimicrobial potential of several combinations of peptide-protein extracts (PCs) consisting of peptide extracts from three native probiotic strains, Lactiplantibacillus plantarum UTNGt2, Lactococcus lactis UTNGt28, and L. plantarum UTNGt21A, alone or in combination with EDTA (ethylenediaminetetraacetic acid) against multidrug-resistant Staphylococcus aureus ATCC1026 and Citrobacter freundii UTNB3Sm1. Based on the antimicrobial assay, among the 19 tested PCs, two (PC11 and PC17) produced a greater zone of inhibition against both pathogens in vitro. Time-killing assays indicated the rapid death of S. aureus after exposure to PC11 and PC17, while C. freundii was rapidly inhibited by PC11 and PC1 (UTNGt2 only), suggesting that the inhibitory action is pathogen and dose-dependent of a particular molecule present in the extract. A marginal inhibitory effect was observed when the peptides were combined with EDTA. Transmission electron microscopy (TEM) revealed the structural membrane damage of both target strains upon interaction with individual peptide extracts. Different degrees of cell deformation, condensed cytoplasm, membrane blebbing, and ghost cell formation with visibly broken cell walls were observed in S. aureus. Likewise, the separation of the cytoplasmic membrane from the outer membrane, ghost cells, along with ovoid and deformed cells with undulated cell walls were observed for C. freundii. Furthermore, scanning electronic microscopy (SEM) analysis revealed different wrinkled and deformed cells covered by debris. A leakage of aromatic molecules was detected for both pathogens, indicating that PCs disrupted the cell wall integrity, inducing cell death. Given their inhibitory action and capacity to induce damage of the cytoplasmic membrane, the selected PCs may serve to slow bacterial growth in vitro; further research is required to prove their efficiency ex vitro to battle against food poisoning and subsequent human infection.